Analysis of Mathematical Problem Solving Abilities in Terms of Students' Motivation and Learning Styles - Huda, Wafiq Nurul; Suyitno, Hardi; Wiyanto, Wiyanto (Journal of Primary Education, 2017)
The purpose of this research is: (1) obtain a picture of the quality of implementation of the model PBL on the ability of solving mathematical problem for the material volume cubes and blocks as well as the surface area of cubes and blocks in class V SD N Karangwotan 02 Pucakwangi Pati, (2) identify the mathematical problem solving ability of students in class V SD N Karangwotan 02 Pucakwangi Pati terms of learning motivation after the application of PBL models, and (3) identify the mathematical problem solving ability of students in class V SD N Karangwotan 02 Pucakwangi Pati terms of learning style after the application of PBL models.This research is a qualitative descriptive study. Analysis of the quality of the learning process judged from phase: (1) planning, (2) implementation, and (3) assessment. While data analysis is done through data reduction, data presentation, and drawing conclusions. The results showed that: (1) the quality of learning by using the model PBL Scientific approach to the achievement of an increase in mathematical problem solving ability of students in class V SD N Karangwotan 02 in both categories, (2) students with learning motivation high, medium, and low have the same pattern differ in resolving mathematical problem solving Polya steps, and (3) the student's learning style visual, auditory, and kinesthetic also both have different patterns in solving a mathematical problem solving with Polya steps.